2018
DOI: 10.1007/s11302-018-9617-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing PKC-dependent membrane P2X3 receptor upregulation in dorsal root ganglia mediated electroacupuncture analgesia in rat painful diabetic neuropathy

Abstract: Painful diabetic neuropathy (PDN) is a common and troublesome diabetes complication. Protein kinase C (PKC)-mediated dorsal root ganglia (DRG) P2X3 receptor upregulation is one important mechanism underlying PDN. Accumulating evidence demonstrated that electroacupuncture (EA) at low frequency could effectively attenuate neuropathic pain. Our previous study showed that 2-Hz EA could relieve pain well in PDN. The study aimed to investigate whether 2-Hz EA relieves pain in PDN through suppressing PKC-mediated DRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 38 publications
3
38
0
1
Order By: Relevance
“…This is because both peripheral (muscle) and central (intrathecal) blockade of P2X3 receptors prevented the static contractioninduced mechanical muscle hyperalgesia. It is widely known that P2X3 receptors are involved in pain signaling of different etiologies and in different tissues, such as neuropathic (partial sciatic ligation and chronic constriction injury) and inflammatory (complete Freund's adjuvant-CFA, carrageenan, formalin-persistent phase) pain in subcutaneous tissue [13,22,41], painful diabetic neuropathy [42], cancer-induced bone pain [43], endometriosis pain [44], articular hyperalgesia [19,45], and visceral pain (colorectal distension, acetic acidinduced abdominal constriction, and trinitrobenzene sulphonic acid colitis) [46,47]. Similar to subcutaneous tissue [22] and knee joint [19] of rats, in this present study, we also demonstrated that ATP, via activation of P2X3 receptors, is an important mediator on the development but not in maintenance of muscle hyperalgesia, since A-317491 prevented the mechanical muscle hyperalgesia when administered before and 30 or 60 min after the start of static contraction, but not 30 or 60 min after the end of it.…”
Section: Discussionmentioning
confidence: 99%
“…This is because both peripheral (muscle) and central (intrathecal) blockade of P2X3 receptors prevented the static contractioninduced mechanical muscle hyperalgesia. It is widely known that P2X3 receptors are involved in pain signaling of different etiologies and in different tissues, such as neuropathic (partial sciatic ligation and chronic constriction injury) and inflammatory (complete Freund's adjuvant-CFA, carrageenan, formalin-persistent phase) pain in subcutaneous tissue [13,22,41], painful diabetic neuropathy [42], cancer-induced bone pain [43], endometriosis pain [44], articular hyperalgesia [19,45], and visceral pain (colorectal distension, acetic acidinduced abdominal constriction, and trinitrobenzene sulphonic acid colitis) [46,47]. Similar to subcutaneous tissue [22] and knee joint [19] of rats, in this present study, we also demonstrated that ATP, via activation of P2X3 receptors, is an important mediator on the development but not in maintenance of muscle hyperalgesia, since A-317491 prevented the mechanical muscle hyperalgesia when administered before and 30 or 60 min after the start of static contraction, but not 30 or 60 min after the end of it.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic neuropathy was modeled by feeding rats with a high-fat and high-sugar diet for 5 weeks plus injecting once streptozocin [43]. Streptozocin injection alone would primarily damage the pancreas only (diabetes type 1), while in combination with the diet used, it caused long-lasting hyperglycemia and histological injury to the sciatic nerve as well (diabetes type 2).…”
Section: P2x3 Receptorsmentioning
confidence: 99%
“…Animal experiments proved that protein kinase C (PKC)-mediated dorsal root ganglia (DRG) P2X3 receptor upregulation is a significant mechanism of PDN [9][10][11] . EA plays an analgesic role by inhibiting the upregulation of PKC-dependent membrane P2X3 in DRG 12 . To our knowledge, a systematic review about the effectiveness of manual acupuncture for treatment of DPN included 25 randomized control trials (RCTs) involving 1649 participants which were published in Chinese 3 .…”
Section: Letter To the Editormentioning
confidence: 99%